2008
DOI: 10.1002/tcr.20155
|View full text |Cite
|
Sign up to set email alerts
|

Stereocontrolled alkylation of unsaturated compounds with alkoxytitanacyclopropane reagents

Abstract: Interaction of titanium(IV) isopropoxide with ethylmagnesium bromide and its higher homologs leads to the generation of alkoxytitanacyclopropane species, which are able to act in the reactions with unsaturated compounds as 1,2-dicarbanionic alkylating agents. The present review is focused on the processes of intermolecular regio- and stereoselective alkylation of carboxylic esters and allylic alcohol derivatives with alkoxytitanacyclopropane reagents. The oxophilicity of the titanium atom and its tendency to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…We report herein a stereoselective alkylation reaction of allylic alcohols by trapping of the presumed alkyltitanium intermediates with suitable electrophiles. This formal S N 2' ethylation reaction by the ethyl Grignard reagent was first reported by the Kulinkovich group, [5] and the stereochemical studies revealed the overall suprafacial stereochemical outcome is due to syn addition of the Kulinkovich reagent through a TiÀO tether and subsequent syn b elimination. [5d,e,6] Our mechanistic analysis implicated the generation of an alkyltitanium intermediate 4 by way of b elimination of 3 at the penultimate stage, which prompted us to investigate in situ elaboration of 4 to broaden the scope of this allylation reaction ( Table 1).…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…We report herein a stereoselective alkylation reaction of allylic alcohols by trapping of the presumed alkyltitanium intermediates with suitable electrophiles. This formal S N 2' ethylation reaction by the ethyl Grignard reagent was first reported by the Kulinkovich group, [5] and the stereochemical studies revealed the overall suprafacial stereochemical outcome is due to syn addition of the Kulinkovich reagent through a TiÀO tether and subsequent syn b elimination. [5d,e,6] Our mechanistic analysis implicated the generation of an alkyltitanium intermediate 4 by way of b elimination of 3 at the penultimate stage, which prompted us to investigate in situ elaboration of 4 to broaden the scope of this allylation reaction ( Table 1).…”
mentioning
confidence: 83%
“…This formal S N 2' ethylation reaction by the ethyl Grignard reagent was first reported by the Kulinkovich group, [5] and the stereochemical studies revealed the overall suprafacial stereochemical outcome is due to syn addition of the Kulinkovich reagent through a TiÀO tether and subsequent syn b elimination.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…This formal S N 2′ ethylation reaction by the ethyl Grignard reagent was first reported by the Kulinkovich group,5 and the stereochemical studies revealed the overall suprafacial stereochemical outcome is due to syn addition of the Kulinkovich reagent through a TiO tether and subsequent syn β elimination 5d,e,6. Our mechanistic analysis implicated the generation of an alkyltitanium intermediate 4 by way of β elimination of 3 at the penultimate stage, which prompted us to investigate in situ elaboration of 4 to broaden the scope of this allylation reaction (Table 1).…”
Section: Methodsmentioning
confidence: 76%